Targeting nitroreductases for selective drug activation: therapeutic perspectives in neglected diseases and tuberculosis - Ruiz, Isabelle Garbin [UNESP]; de Andrade, Isabela Dotalli [UNESP]; Matuhara, Laís Yukari Sposati [UNESP]; da Cunha, Pamela Souza Tada [UNESP]; Gini, Ana Luísa Rodriguez [UNESP]; João, Emílio Emílio [UNESP]; Dos Santos, Jean Leandro [UNESP]; Scarim, Cauê Benito [UNESP] (Elsevier, 2025)
Current treatments for neglected tropical diseases (NTDs) and tuberculosis (TB) face major challenges, including toxicity, limited efficacy, and the emergence of drug resistance. These limitations highlight the urgent need for more selective and effective chemotherapeutic strategies. Nitroreductases (NTRs) are pathogen-specific flavin-dependent oxidoreductases that catalyze the bioactivation of nitroaromatic prodrugs into cytotoxic metabolites, enabling selective chemotherapy against parasites and mycobacteria. In this review, we provide a systematic analysis that differs from previous works by emphasizing the enzymatic and structural features of NTR1, NTR2, and Ddn, as well as their potential to guide selective prodrug design. A curated set of nitroheterocyclic compounds was analyzed, representing diverse functional classes such as benzoquinones (11), nitroimidazopyridines (51), nitro-heteroaromatics (74), benzofuranones (80, 83), and 1,3,4-oxadiazoles (111), which were evaluated in terms of enzymatic activation profiles, structure-activity relationship (SAR) trends, and predicted pharmacokinetic parameters relevant to oral bioavailability. By integrating enzyme-specific activation, physicochemical properties, and resistance-associated mutations into comparative tables, this review delivers a comprehensive resource that bridges medicinal chemistry, bioorganic chemistry, and rational drug design. Collectively, our analysis highlights the translational value of NTR-mediated prodrug strategies and positions pathogen-specific nitroreductases as promising metabolic triggers for the next generation of therapies against neglected tropical and mycobacterial diseases.